Skeletal Muscle Ribosome and Mitochondrial Biogenesis in Response to Different Exercise Training Modalities - Mesquita, Paulo H. C.; Vann, Christopher G.; Phillips, Stuart M.; McKendry, James; Young, Kaelin C.; Kavazis, Andreas N.; Roberts, Michael D. (Frontiers in Physiology, 2021)
Skeletal muscle adaptations to resistance and endurance training include increased ribosome and mitochondrial biogenesis, respectively. Such adaptations are believed to contribute to the notable increases in hypertrophy and aerobic capacity observed with each exercise mode. Data from multiple studies suggest the existence of a competition between ribosome and mitochondrial biogenesis, in which the first adaptation is prioritized with resistance training while the latter is prioritized with endurance training. In addition, reports have shown an interference effect when both exercise modes are performed concurrently. This prioritization/interference may be due to the interplay between the 5' AMP-activated protein kinase (AMPK) and mechanistic target of rapamycin complex 1 (mTORC1) signaling cascades and/or the high skeletal muscle energy requirements for the synthesis and maintenance of cellular organelles. Negative associations between ribosomal DNA and mitochondrial DNA copy number in human blood cells also provide evidence of potential competition in skeletal muscle. However, several lines of evidence suggest that ribosome and mitochondrial biogenesis can occur simultaneously in response to different types of exercise and that the AMPK-mTORC1 interaction is more complex than initially thought. The purpose of this review is to provide in-depth discussions of these topics. We discuss whether a curious competition between mitochondrial and ribosome biogenesis exists and show the available evidence both in favor and against it. Finally, we provide future research avenues in this area of exercise physiology.